Impact of cryoprotectant-free sperm vitrification in pulled-glass capillary on sperm parameters and DNA integrity: A lab trial study - Minh Tam Le; Trung Van Nguyen; Thai Thanh Thi Nguyen; Hong Nhan Thi Dang; Quoc Huy Vu Nguyen (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: Vitrification is a recently introduced yet widely applied assisted reproduction technique. So far, the effects of the chemicals and devices in vitrification on sperm motility and DNA integrity are still unclear. Objective: This study aimed to examine sperm quality, as determined by semen analysis and sperm DNA integrity when vitrified with or without cryoprotectant agents (CPAs) using pulled-glass capillaries. Materials and Methods: Between February and June 2020, 50 infertile men from the Hue Center for Reproductive Endocrinology and Infertility, Hue University of Medicine and Pharmacy, Vietnam, were enrolled. Sperm samples, prepared using the swim-up technique, were divided into 2 groups: vitrification with CPAs (group 1) and without CPAs (group 2). Vitrified sperm samples were preserved in 10 µL pulled-glass capillaries. Motility, sperm membrane integrity, and the DNA fragmentation index were tested. Results: Sperm motility in vitrified media with CPAs (54.4 ± 11%) was statistically higher than in media without CPAs (51.14 ± 10.6%, p < 0.05). CPAs did not affect sperm membrane integrity or large halo ratio (71.34 ± 8.47 vs. 70.38 ± 8.11 and 50.84 ± 18.92 vs. 51.98 ± 19.44, respectively). Group 2 exhibited a lower DNA fragmentation index than group 1 after vitrification (14.2 ± 8.47 vs. 12.60 ± 9.03, p = 0.021). Conclusion: Using a pulled-glass capillary for sperm vitrification, the presence of CPAs in the vitrification medium resulted in higher progressive motility and lower DNA fragmentation index than the medium without CPAs.